The flexible lyric - Voigt, Ellen Bryant, 1943- (Life of poetry., 1999)
The author contends that the traditional form of writing "lyric" has been deprecated as a genre, in favor of modern narrative and drama. She presents her views that lyrics are as powerful and poignant an artform as they have ever been by examining structure and meaning in the verse form.